Comparative Studies on the Adsroption Properties of Powdered Activated Carbon and Propenoic Acid Modified Sawdust in the Treatment of Secondary Palm Oil Mill Effluent (Biological Sciences - PJSIR, 2006)
Propenoic acid monomer was used to modify pulped cellulosic materials (sawdust). The sorption properties of the propenoic acid modified sawdust (PAMS) were compared with those of powdered activated carbon (PAC) in the tertiary treatment of palm oil mill effluent, previously clarified with iron(III) chloride plus lime (secondary effluent). The adsorption processes were effected in a fluidized bed reactor (FBR) at a pressure of 80 kiloNewton per meter square (kNm-2). Optimum amount of PAC and PAMS used for the fluidized adsorption of contaminants from the secondary palm oil mill effluent (POME) were 2.5 g/l and 4.0 g/l, respectively. These sorption processes were found to be optimum at 10 min and 50 min for PAC and PAMS, respectively. At optimum sorption conditions, removal differen- tials of 28.6%/g chemical oxygen demand, 19.1%/g suspended solids, and 19.3%/g colour in favour of PAC were established. The application of optimum conditions for adsorption, for both adsorbents, to the bulk treatment of the palm oil mill effluent yielded a clear effluent with wider reuse applicability.